The Central Asian states’ role in the world mining industry - Aleksandr K Kirsanov; Evgenii P Volkov; Georgij S Kurchin; Natalia A Shkaruba; Ravil Z Nafikov; Umarjon R Teshaev (Journal of Degraded and Mining Lands Management, 2022)
The growing needs of mankind for minerals predetermine a systematic increase in the scope of mining operations. However, it is known that mineral resources are not evenly distributed in the bowels of the earth; therefore, due to their production, some regions of our planet can significantly outstrip other regions in their technical and, as a result, economic development; hence, the constant need to extract more minerals in order to develop the domestic industry and to strengthen the economy. This paper is devoted to the Central Asian states, their internal structure, economic integration into the world economy, and the mining sector development as the basis of a successful model for the development of the country as a whole. The study summarizes and analyzes the political system and socio-economic conditions in the Central Asian states. It presents a brief overview of the scale of mining operations; provides information about the mining industry structure in each country and the proceeds from its sales. Taking the Central Asian states as an example, we demonstrate the importance of the mining sector as an integral part of a country’s domestic economic structure.